USE OF COACHING TECHNOLOGIES IN AUDITORIUM TRAINING - Makhzuna Sh. Ismatova (International Scientific and Current Research Conferences, 2023)
The educational standards of modern higher education pose ever new challenges for teachers: a teacher, who can be considered a professional, has to not only teach students his subject, but also act as a researcher, innovator, coach, who combines various roles and diverse functions. The innovative function includes the ability to creatively approach the solution of pedagogical problems, as well as to use the rich experience of predecessors who sought and successfully applied the means of training, development and education. Without taking into account the psychological aspects, without organizing a multifaceted and complexly organized support for the learning process, it is impossible to imagine any discipline of the humanitarian cycle, especially the teaching of a foreign language.